Pneumocystis jirovecii colonisation in HIV‐positive and HIV‐negative subjects in Cameroon. Issue 6 (19th March 2014) - Riebold, D.; Enoh, D. O.; Kinge, T. N.; Akam, W.; Bumah, M. K.; Russow, K.; Klammt, S.; Loebermann, M.; Fritzsche, C.; Eyong, J. E.; Eppel, G.; Kundt, G.; et al.
Abstract Objective To determine the prevalence of Pneumocystis pneumonia (PCP), a major opportunistic infection in AIDS patients in Europe and the USA, in Cameroon. Materials and methods Induced sputum samples from 237 patients without pulmonary symptoms (126 HIV‐positive and 111 HIV‐negative outpatients) treated at a regional hospital in Cameroon were examined for the prevalence of Pneumocystis jirovecii by specific nested polymerase chain reaction (nPCR) and staining methods. CD4 counts and the history of antiretroviral therapy of the subjects were obtained through the ESOPE database system. Results and conclusion Seventy‐five of 237 study participants (31.6%) were colonised with Pneumocystis, but none showed active PCP. The Pneumocystis colonisation rate in HIV‐positive subjects was more than double that of HIV‐negative subjects (42.9% vs. 18.9%, P < 0.001). In the HIV‐positive group, the colonisation rate corresponds to the reduction in the CD4 lymphocyte counts. Subjects with CD4 counts >500 cells/μl were colonised at a rate of 20.0%, subjects with CD4 counts between 200 and 500 cells/μl of 42.5%, and subjects with CD4 counts <200 cells/μl of 57.1%. Colonisation with Pneumocystis in Cameroon seems to be comparable to rates found in Western Europe. Prophylactic and therapeutic measures against Pneumocystis should be taken into account in HIV care in western Africa.